2016
DOI: 10.2147/hp.s103088
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate availability affects tumor implantation-take rate and increases tumor rejection in Gulo–/– mice

Abstract: In solid tumors, HIF1 upregulates the expression of hundreds of genes involved in cell survival, tumor growth, and adaptation to the hypoxic microenvironment. HIF1 stabilization and activity are suppressed by prolyl and asparagine hydroxylases, which require oxygen as a substrate and ascorbate as a cofactor. This has led us to hypothesize that intracellular ascorbate availability could modify the hypoxic HIF1 response and influence tumor growth. In this study, we investigated the effect of variable intracellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…The co-factor role is specific to ascorbate ( Myllyla et al, 1978 ), which is structurally specific for the hydroxylase active site ( Kaczmarek et al, 2009 ). When cells are deficient in ascorbate, HIF hydroxylase activity is compromised and HIF transcription activity is increased, particularly in response to conditions of mild or moderate hypoxia ( Knowles et al, 2003 ; Vissers et al, 2007 ; Kuiper et al, 2014a ; Campbell et al, 2016a ). These observations have led to the hypothesis that increasing ascorbate supply to cancer cells could stimulate the activity of the HIF hydroxylases and decrease the activation of the HIFs, thereby slowing tumor growth rates.…”
Section: Anti-cancer Activities Of Ascorbatementioning
confidence: 99%
See 1 more Smart Citation
“…The co-factor role is specific to ascorbate ( Myllyla et al, 1978 ), which is structurally specific for the hydroxylase active site ( Kaczmarek et al, 2009 ). When cells are deficient in ascorbate, HIF hydroxylase activity is compromised and HIF transcription activity is increased, particularly in response to conditions of mild or moderate hypoxia ( Knowles et al, 2003 ; Vissers et al, 2007 ; Kuiper et al, 2014a ; Campbell et al, 2016a ). These observations have led to the hypothesis that increasing ascorbate supply to cancer cells could stimulate the activity of the HIF hydroxylases and decrease the activation of the HIFs, thereby slowing tumor growth rates.…”
Section: Anti-cancer Activities Of Ascorbatementioning
confidence: 99%
“…There is a growing body of evidence consistent with this hypothesis. Investigations with the vitamin C-dependent Gulo -/- mouse have indicated a strong association between tumor ascorbate content, HIF activation and tumor growth in vivo following variable dietary intake or intra-peritoneal injection of pharmacological ascorbate ( Campbell et al, 2015 , 2016a ). The daily administration of high dose vitamin C to tumor-bearing Gulo -/- mice indicated that HIF-1 transcriptional activity was depressed in association with ascorbate uptake.…”
Section: Anti-cancer Activities Of Ascorbatementioning
confidence: 99%
“…Because of the pleiotropic functions of vitamin C, optimizing its levels in the body through diet and supplementation is likely to be of benefit to oncology patients. In support of this premise, studies in a vitamin C-requiring mouse model indicate that oral vitamin C supplementation of these animals can impair the development of tumors and can also increase the rejection rate of implanted tumor cells ( Campbell et al, 2016a ; Cha et al, 2016 ). This suggests an important role for vitamin C in host defense against cancer.…”
Section: Introductionmentioning
confidence: 96%
“…Subgroup III, the Jumonji C (JmjC) domain containing histone lysine demethylases (JmjC-KDMs), erases the methyl group on lysine residues of histones 12 . Subgroup IV, the hypoxia-inducible factor (HIF) hydroxylases, catalyzes hydroxylation on specific proline and asparagine residues of the transcription factor HIF-1α 13 . Studies confirmed that ascorbic acid regulates Tet, JmjC domain containing enzymes and HIF hydroxylases, to modulate dynamically the epigenetic status of DNA/histone methylation and HIF-1α activity 6 , 9 , 12 14 .…”
Section: Introductionmentioning
confidence: 99%